Class of Multivalent Analytic Functions Defined by a Linear Operator. (9th January 2013) - Frasin, B. A.
Abstract : Making use of the linear operator J p m ( λ, l ) defined in (Prajapat, 2012), we introduce the class 𝔹 p m ( λ, l, μ, α ) of analytic and p -valent functions in the open unit disk 𝒰 . Furthermore, we obtain some sufficient conditions for starlikeness and close-to-convexity and some angular properties for functions belonging to this class. Several corollaries and consequences of the main results are also considered.